Insufficient Fluid Intake during Fishing as a Determinant of Hypertension among Traditional Fishermen in Coastal Soropia - Cholik Harun Rosjidi; Siti Umrana; Risnawati Risnawati; Herman Herman (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Hypertension is a major public health problem and an important risk factor for cardiovascular disease, particularly among informal workers such as traditional fishers who are exposed to harsh working conditions and limited healthy lifestyle choices. Coastal fishers generally work in hot environments, spend long fishing hours, smoke, and have limited access to safe drinking water during fishing activities. This study aims to analyze the association between sociodemographic characteristics, behavioral factors, and drinking patterns during fishing activities with hypertension among traditional fishers. A cross-sectional analytical study was conducted among 168 fishers in Soropia Regency, Southeast Sulawesi, Indonesia, recruited using proportional random sampling. Univariate analysis showed a high prevalence of hypertension (50.6%), with smoking behaviors and inadequate drinking patterns during fishing being the dominant factors. Bivariate analysis showed that age ≥50 years (p=0.030; OR=2.30; 95% CI: 1.08–5.04), education level (p=0.025; OR=2.04; 95% CI: 1.09–3.83), smoking behavior (p=0.001; OR=3.62; 95% CI: 1.60–8.08), and inadequate drinking pattern (p=0.003; OR=2.60; 95% CI: 1.38–4.92) were significantly associated with hypertension. Multivariate analysis confirmed that education (p=0.040; OR=2.177; 95% CI: 1.034–4.584), smoking (p=0.005; OR=3.667; 95% CI: 1.476–9.111), age ≥50 years (p=0.019; OR=2.903; 95% CI: 1.196–7.046), and inadequate drinking pattern during fishing activities (p=0.001; OR=3.350; 95% CI: 1.628–6.892) remained the dominant factors associated with hypertension. These findings call for structured, community-based preventive interventions in coastal fishing populations that are explicitly calibrated to the magnitude of the identified risks: smoking cessation programs are prioritized given the 3.7-fold increased risk among smokers (OR=3.667), while mandatory hydration protocols during fishing trips are warranted due to the 3.4-fold increased risk associated with inadequate fluid intake (OR=3.350). Furthermore, targeted blood pressure screening for fishers aged ≥50 years (OR=2.903) and context-sensitive health education for those with lower educational levels (OR=2.177) should be integrated into coastal primary health care programs to ensure comprehensive and proportional risk reduction based on evidence Keywords: Hypertension, Public Health, Fishermen, Coastal Areas, Inadequate Fluid Intake